2016
DOI: 10.1214/16-aoas921
|View full text |Cite
|
Sign up to set email alerts
|

What we look at in paintings: A comparison between experienced and inexperienced art viewers

Abstract: How do people look at art? Are there any differences between how experienced and inexperienced art viewers look at a painting? We approach these questions by analyzing and modeling eye movement data from a cognitive art research experiment, where the eye movements of twenty test subjects, ten experienced and ten inexperienced art viewers, were recorded while they were looking at paintings.Eye movements consist of stops of the gaze as well as jumps between the stops. Hence, the observed gaze stop locations can … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Experts also tend to make less frequent and shorter fixations on narrative elements (Kristjanson & Antes, 1989;Pihko et al, 2011;Vogt & Magnussen, 2007). Ylitalo et al (2016) found that experts tend to have shorter fixation durations and less variability in fixation durations than novices. Fedorovskaya et al (2017) found less local viewing by experts and less re-fixations on already attended areas.…”
Section: Expertisementioning
confidence: 99%
“…Experts also tend to make less frequent and shorter fixations on narrative elements (Kristjanson & Antes, 1989;Pihko et al, 2011;Vogt & Magnussen, 2007). Ylitalo et al (2016) found that experts tend to have shorter fixation durations and less variability in fixation durations than novices. Fedorovskaya et al (2017) found less local viewing by experts and less re-fixations on already attended areas.…”
Section: Expertisementioning
confidence: 99%
“…Back to the specific topic of our study, even Cultural Heritage can benefit from eye-tracking studies [36]. In Reference [37], eye movement was evaluated by a spatio-temporal point process model for comparing the eye movements of experienced and inexperienced art viewers. However, the model developed by the authors is not accurate for studying the complete dynamics of the fixation process, since it does not capture how the fixation process changes over time.…”
Section: Related Workmentioning
confidence: 99%
“…Bottom-up factors were indicated as a strong role in children, while in adults the observed patterns were similar in both phases. In [25] eye movement was analysed by the simple model, a spatio-temporal point process model, to compare the eye movements of experienced and inexperienced art viewers. However, the model developed in this paper is not good enough for studying the complete dynamics of the fixation process, since it does not capture how the fixation process is changing in time.…”
Section: Related Workmentioning
confidence: 99%